Foraging behavior of an invasive alien hornet (Vespa velutina) at Apis mellifera hives in Korea: Foraging duration and success rate. Issue 3 (17th March 2021) - Choi, Moon Bo
Abstract: The introduction of an invasive alien hornet ( Vespa velutina ) to Korea in 2003 has caused severe economic impacts on the beekeeping industry. We observed this hornet attacking honeybees at hives and need to develop control and management approaches for the hornet. We recorded the duration of foraging attacks and the success rate of V. velutina at beehives from July to October. The foraging duration was 40–50 s from July to early August but fell to ~20 s from the end of August, and 10 s was recorded in September. Twenty seconds was recorded at the beginning of October and foraging duration increased to 80 s at the end of October. This seems to be because the number of experienced, mature workers within the V. velutina nest is high from August. The foraging success was 80.63% overall but exceeded 96% in September. This is much higher than the success rate in the native region, which means that the local honeybees have not yet developed adequate defense mechanisms against predation by this new, invasive species.